Using the Altman’s Z-score formula to assess the bankruptcy risk of state - owned construction enterprises in Vietnam - Thi Khanh Van, Hoang; Quoc Toan, Nguyen; Van Tuan, Le (Edelweiss Applied Science and Technology, 2024)
In the current economic situation affected by epidemics, wars, recessions, etc., construction enterprises in Vietnam in general and state – owned construction enterprises in particular face many difficulties to maintain performance efficiency. On the other hand, the policies of restructuring and equitization of state-owned enterprises also have a strong impact on the financial management of construction enterprises in Vietnam. This study uses data from financial statements of 22 state-owned construction enterprises in Hanoi from 2017 to 2021 to calculate the Altman Z-score formula. The Altman Z-score is a linear combination of four or five common business ratios, weighted by coefficients. Z-scores are used to predict corporate defaults and an easy-to-calculate control measure for the financial distress status of enterprises with high reliability. The research results show that a few enterprises are in the "safe" zone and "grey" one while most are in "distress" zone. The cause of inefficient business performance is that the revenue and profit ratio to total assets of state-owned construction enterprises to decrease sharply, the ratio of working capital to total assets is low. Moreover, the ratio of equity to total debt is the most important reason for the low Z-score, which means predicting a high risk of bankruptcy in state-owned construction enterprises. The evidence base from the research results is used to propose 5 solutions to reduce the risk of bankruptcy and improve the efficiency of financial management of enterprises.